A Virus Propagation Model and Optimal Control Strategy in the Point-to-Group Network to Information Security Investment. (3rd June 2021) - Feng, Liping; Han, Ruifeng; Wang, Hongbin; Zhao, Qingshan; Fu, Chengli; Han, Qi
Abstract : Epidemiological dynamics is a vital method in studying the spread of computer network viruses. In this paper, an optimal control measure is proposed based on the SEIR virus propagation model in point-to-group information networks. First, considering the need for antivirus measures in reality, an optimal control problem is introduced, and then a controlled computer virus spread model in point-to-group information networks is established. Second, the optimal control measure is formulated by making a tradeoff between control cost and network loss caused by virus intrusion. Third, optimal control strategies are theoretically investigated by Pontryagin's maximum principle and the Hamiltonian function. Finally, through numerical simulations, effective measures for controlling virus spread in point-to-group information networks are proposed.